Reduction of Dispersant Pollutant (Linear Alkylbenzene Sulfonate) by Mangrove Plant (Rhizophora mucronata) - Syahril Nedi; Irwan Effendi; Afrizal Tanjung; Elizal Elizal (Jurnal Natur Indonesia, 2023)
Linear alkylbenzene sulfonate (LAS) is the main component of dispersants that function as cleaners of various materials. The increasing use of LAS causes this compound to dominantly pollute coastal waters. Phytoremediation is the most environmentally safe alternative to physical and chemical methods. One of the potential plants as a phytoremediator is Rhizophora mucronata. This research is an experiment as an application of LAS pollutant control by R.mucronata plants in waters. After acclimatization and preliminary tests, the implementation of LAS phytoremediation tests by R. mucronata plants in seawater media was carried out at concentrations of A1: 25 mg/L, A2: 100 mg/L, A3: 175 mg/L, A4: 250 mg/L, and A5: 325 mg/L and control (Control without plants) as a simulation of the presence of pollutants in coastal waters. The method used was a completely randomized design (CRD) with one treatment and 3 replications. The reduction of LAS concentration in the test media and its effect on R.mucronata leaf chlorophyll and dissolved oxygen were analyzed at week 2 to week 4. The analysis results showed that LAS compounds could be reduced to 91.48% at week 2 and 97.40% at week 4. Plant Water quality parameters (dissolved oxygen, temperature and pH) were measured daily. Based on the study results, LAS can be reduced by R.mucronata plants 87-90.4% in week 2 and 95.1-97.4% in week 4. LAS exclusion by plants had a significant impact on the reduction of leaf chlorophyll content until week 4. LAS reduction by R.mucronata in the media can increase dissolved oxygen content as an indication of improved water quality. R.mucronata plants can be used as an alternative to control LAS pollution in waters